2019
DOI: 10.3390/ma12223750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Needling Parameters and Manufacturing Porosities on the Effective Thermal Conductivity of a 3D Carbon–Carbon Composite

Abstract: Needle-punching is used as an alternative to expensive and sophisticated three-dimensional (3D) weaving processes to prepare a 3D composite. In this study, a 3D needled carbon–carbon (C/C) composite structure was examined using X-ray tomography and scanning electron microscopy (SEM). The effects of manufacturing porosities, needling diameter and needling density on the thermal conductivity of the composite were determined through multiscale finite-element modelling. The degradation of thermal conductivity caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…These results correlate well with the results obtained by µCT analysis. A similar effect has been observed in previous studies [ 64 , 65 , 66 ], which confirmed the influence of needle-punching density on thermal conductivity by producing a series of CFs with different needle-punching densities. Therefore, the combined effects of the conductive nature and orientation of the carbon fibers influences the anisotropic heat transfer behavior.…”
Section: Resultssupporting
confidence: 91%
“…These results correlate well with the results obtained by µCT analysis. A similar effect has been observed in previous studies [ 64 , 65 , 66 ], which confirmed the influence of needle-punching density on thermal conductivity by producing a series of CFs with different needle-punching densities. Therefore, the combined effects of the conductive nature and orientation of the carbon fibers influences the anisotropic heat transfer behavior.…”
Section: Resultssupporting
confidence: 91%
“…The problem of low thermal conductivity of materials can be solved only by improving the thermal conduction path by constructing the material structure. Recently, researchers have carried out extensive research by constructing a three-dimensional (3D) filler network structure in the resin matrix, which is considered as a promising strategy in many fields. By assembling some fibrous one-dimensional fillers with a high aspect ratio (metal silver, carbon nanotubes, and carbon fibers) or two-dimensional fillers (graphite flakes, graphene) to form a 3D network heat conduction structure, direct low thermal resistance and rich heat conduction paths can be provided in the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the preform is impregnated and carbonized to construct the 4D C/C composites [27]. The prediction of the effective thermal conductivities of 4D C/C composites can be carried out on the unit cells at meso-scale, similar to other composites with periodic structure [28,29]. Carbon fiber rods and carbon fiber bundles can be regarded as transverse isotropic composite materials [30].…”
Section: Introductionmentioning
confidence: 99%